Do Laryngologists and General Otolaryngologists Manage Laryngopharyngeal Reflux Differently?. (8th January 2020) - Lechien, Jerome R.; Allen, Jacqueline; Mouawad, Francois; Ayad, Tareck; Barillari, Maria Rosaria; Huet, Kathy; Crevier‐Buchman, Lise; Hans, Stéphane; Karkos, Petros D.; Eun, Young‐Gyu; Bobin, Francois; Saussez, Sven; et al.
Abstract : Objective: To investigate current practices of laryngologists and non‐laryngologists in management of Laryngopharyngeal Reflux (LPR). Methods: An online survey was sent to members of otolaryngology societies about LPR, and subgroup analysis was performed between laryngologists and non‐laryngologists. This survey was conducted by the LPR Study Group of Young Otolaryngologists of the International Federation of Otolaryngological Societies. Results: A total of 535 otolaryngologists completed the survey. Among them, 127 were laryngologists and 408 were non‐laryngologists. Collectively, symptoms most commonly attributed to LPR are cough after lying down/meal, throat clearing, and acid brash; most common findings are thought to be arytenoid erythema and posterior commissure hypertrophy. Respectively, 12.5% and 5% of non‐laryngologists and laryngologists believe that ≥50% of LPR patients suffer from heartburn ( P = .010). Non‐laryngologists are more aware about some extra‐laryngeal findings associated with LPR (eg, pharyngeal erythema) than laryngologists. Neither laryngologists nor non‐laryngologists associated development of benign lesions of the vocal folds with reflux. The management of LPR substantially differs between groups, with laryngologists indicating increased awareness of (impedance)‐pH monitoring as well as the prevalence and treatment of nonacid/mixed LPR. Conversely, non‐laryngologists are much more likely to include gastroenterology referral in their management of presumed LPR. Respectively, 44.8% and 27.6% of non‐laryngologists and laryngologists believe themselves not sufficiently knowledgeable about LPR. Conclusions: Significant differences exist between laryngologists and non‐laryngologists in diagnosis and treatment of LPR. Overall only one‐third of responders believe themselves to be sufficiently educated about LPR. Level of Evidence: 4 Laryngoscope, 130:E539–E547, 2020